Diversifikasi Produk Recycling di Bank Sampah KGS Melalui Pembuatan Sabun Cair dari Minyak Jelantah - Ahadito, Bijak Riyandi; Palapa, Neza Rahayu; Mukaromah, Laela; Nawawi, Rizki Andini (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the knowledge and skills of administrators, customers, and surrounding community members of KGS Waste Bank in Palembang in utilizing used cooking oil waste through the application of simple technology to produce liquid soap with practical and economic value. The activity was carried out using a socialization approach combined with training on the production of liquid soap from used cooking oil through a cold saponification process. Evaluation instruments consisted of pre-test and post-test assessments, which were subsequently analyzed descriptively. The results of the program showed an improvement in participants’ understanding of the liquid soap production process from used cooking oil, as indicated by an increase in the average score of 16.94 points in the post-test. This activity successfully opened opportunities for product diversification among the program partners and is expected, through this transfer of knowledge, to enrich the portfolio of recycled products they produce.